A belief rule based (BRB) system to assess asthma suspicion - Rahaman, Saifur; Hossain, Mohammad Shahadat (16th Int'l Conf. Computer and Information Technology, 2014)
Asthma is a common chronic inflammatory disease. A belief rule based Clinical Decision Support System (CDSS) of asthma suspicion is enhancing the accuracy of suspicion. This research paper presents out the development of a Belief rule based (BRB) system to assess Asthma suspicion by using signs and symptoms. The recently developed generic belief rule-based inference methodology by using the evidential reasoning approach (RIMER) has been considered to develop this BRB system. This system can deal with various types of uncertainties, found in clinical sings, symptoms, and clinical domain knowledge. The knowledge base of this system has been constructed by taking account of real patient data and consultation with specialists. The practical case studies provided to test this system. It has been observed that the proposed model is effective and can generate better prediction than from manual system (usually carried out by specialist) in terms of accuracy.